Sports Institute Northern Ireland (University of Ulster, 2007)
The Sports Institute Northern Ireland (SINI) is a partnership between Sport Northern Ireland and the University of Ulster. SINI aims to provide specialist services and key facilities for up to 120 able bodied and disabled, international and national, sportsmen and women, to improve their competitive capacity within the worlds sporting arena.